Climate change, species range shifts and dispersal corridors: a portfolio of spatial conservation models - Alagador, Diogo (2015)
The notion that conservation areas are static geographical units for biodiversity conservation should be revised when planning for climate‐change adaptation. Since species are expected to respond to climate change by shifting their distributions, conservation areas can lose the very same species that justified their designation. Methods exist to take into account the potential effects of climate on spatial priorities for conservation. One of such methods involves the identification of time‐ordered linkages between conservation areas (hereafter termed climate‐change corridors), thus enabling species tracking their suitable changing climates. We critically review and synthesise existing quantitative approaches for spatial conservation planning under climate change. We extend these approaches focusing on the identification of climate‐change corridors, using three alternative models that vary on the objective function (minimum cost or maximum benefit sought) and on the nature of conservation targets (area‐based or persistence probabilities). The three models for establishing climate‐change corridors are illustrated with a case study involving two species distributed across the Iberian Peninsula. The species were modelled in relation to climate‐change scenarios using ensembles of bioclimatic models and theoretical dispersal kernels. The corridors obtained are compared for their location, the temporal sequence of priorities, and the effectiveness with which solutions attain persistence and cost objectives. By clearly framing the climate‐change corridors problem as three alternative models and providing the corresponding mathematical descriptions and solving tools, we offer planners a wide spectrum of models that can be easily adapted to a variety of conservation goals and constraints.